The organizational culture of family firms as a key factor of competitiveness - Vallejo-Martos, Manuel Carlos (Journal of Business Economics and Management, 2011)
In the current research work we build and test a model for the analysis and management of the organizational culture of family firms based on the main arguments of neo-institutional theory and transformational leadership theory. The model we have built allows us to test for the existence of positive relations between the values defining the second level of organizational culture (commitment, harmony, long term orientation and customer service and performance, measured through variables, such as profitability, survival and group cohesion. The model will prove to be useful tool to exploit the competitive potential that the organizational culture represents for this type of firms. Article in English. Pagrindinis šeimos įmonių konkurencingumo veiksnys – organizacinė kultūra Santrauka. Šiame straipsnyje, atsižvelgiant į dabartinę mokslinių tyrimų kryptį, analizuojama organizacinė šeimos įmonių kultūra, kuri grindžiama neoinstitucine teorija ir transformacinio vadovavimo teorijos modeliu. Modelyje pateikiamos teigiamos santykių vertės, nustatančios organizacinę kultūrą (įsipareigojimus, darną, ilgalaikę orientaciją ir klientų aptarnavimą) bei veiklos rezultatus, išmatuotus naudojant tokius kintamuosius kaip pelningumas, išlikimas ir grupės egzistavimo sanglauda. Modelis rodo, kokios priemonės būtų naudingos siekiant išnaudoti konkurencinį tokio tipo įmonių potencialą. Reikšminiai žodžiai: šeima, įmonė, vertybės, organizacinė kultūra.